2016
DOI: 10.1161/jaha.115.002767
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N‐Oxide Promotes Vascular Inflammation Through Signaling of Mitogen‐Activated Protein Kinase and Nuclear Factor‐κB

Abstract: BackgroundThe choline‐derived metabolite trimethylamine N‐oxide (TMAO) has been demonstrated to contribute to atherosclerosis and is associated with coronary artery disease risk.Methods and ResultsWe explored the impact of TMAO on endothelial and smooth muscle cell function in vivo, focusing on disease‐relevant outcomes for atherogenesis. Initially, we observed that aortas of LDLR −/− mice fed a choline diet showed elevated inflammatory gene expression compared with controls. Acute TMAO injection at physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
544
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 645 publications
(564 citation statements)
references
References 41 publications
(90 reference statements)
11
544
1
8
Order By: Relevance
“…This is, in large part, due to the lack of understanding of the molecular sensor for TMAO (that is, the TMAO receptor). Although there is evidence that TMAO can function as an important osmolyte in biological systems 78,79 , more recent evidence suggest that TMAO can rapidly signal to cells within minutes 8,80 . In isolated platelets, brief exposures to physiological levels of TMAO can potentiate thrombin-induced calcium release 8 .…”
Section: Microbial Metabolites In Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, in large part, due to the lack of understanding of the molecular sensor for TMAO (that is, the TMAO receptor). Although there is evidence that TMAO can function as an important osmolyte in biological systems 78,79 , more recent evidence suggest that TMAO can rapidly signal to cells within minutes 8,80 . In isolated platelets, brief exposures to physiological levels of TMAO can potentiate thrombin-induced calcium release 8 .…”
Section: Microbial Metabolites In Cvdmentioning
confidence: 99%
“…In isolated platelets, brief exposures to physiological levels of TMAO can potentiate thrombin-induced calcium release 8 . Likewise, treatment with TMAO in endothelial cells or smooth muscle cells, or direct injection in vivo, was shown to rapidly induce the activation of mitogen-activated protein kinases and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), or the upregulation of downstream adhesion proteins on aortic endothelial cells 80 . The kinetics of these TMAO-induced signaling responses strongly suggest that host cells may possess a dedicated receptor or sensor system to transduce the TMAO signal to an appropriate cellular response (FIG 2).…”
Section: Microbial Metabolites In Cvdmentioning
confidence: 99%
“…18 Several pro-inflammatory mediators including Cyclo-oxygenase-2 (COX-2), E-Selectin and Intracellular Adhesion Molecule-1 (ICAM-1) were upregulated in the aortic tissue of low-density lipoprotein receptor knock-out (LDLr-/-) mice receiving dietary choline or intraperitoneal TMAO. 35 In vitro, TMAO enhanced leucocyte adhesion to endothelial cells in an NF-κB-dependent manner. 35 Furthermore, enhanced platelet activation and adhesion has been observed following intraperitoneal TMAO injections in an in vivo carotid artery injury model.…”
Section: Tmao As a Mediator Of CV Disease: Experimental Datamentioning
confidence: 99%
“…35 In vitro, TMAO enhanced leucocyte adhesion to endothelial cells in an NF-κB-dependent manner. 35 Furthermore, enhanced platelet activation and adhesion has been observed following intraperitoneal TMAO injections in an in vivo carotid artery injury model. 36 …”
Section: Tmao As a Mediator Of CV Disease: Experimental Datamentioning
confidence: 99%
“…Studies on both in vivo and in vitro cultured human aortic endothelial cells and vascular smooth muscle cells showed that elevated levels of TMAO induce expression of proinflammatory cytokines and adhesion molecules mediated by the NF-κB signaling pathway [18]. TMAO enhances monocyte activation as well as adhesion by activating endothelial cells to express VCAM-1 [19,20].…”
mentioning
confidence: 99%